The responses of roselle (Hibiscus sabdariffa L.) to the application of plant growth regulators in developing seedless fruit and maintaining its quality - Siti Rabiatul Adawiyah Sahidon,; Nor Afifah Abd Rahman,; Wan Zaliha Wan Sembok, (Penerbit Universiti Kebangsaan Malaysia, 2022)
Seedless fruit is a fruit developed to possess no mature seeds. Today lifestyle, consumers and/or manufacturers prefer fruit without seeds as removing it is time-consuming and troublesome. Indeed, seedless fruits have better organoleptic attributes than seeded fruits. To produce seedless roselle and maintain its postharvest quality, various spray applications of synthetic and naturally occurring plant growth regulators were investigated. Roselle is perishable and non-climacteric fruit that is exposed to rapid postharvest physiological deterioration following harvest. Thus, producing seedless fruit may reduce time and labor costs during the removing seed process. The experimental treatments were arranged in randomized complete block design with different types of plant growth regulators and spray applications. The PGRs treatments at varying frequencies were sprayed on roselle flower buds at 35, 45, 55, and 65 days after transplanting (DAT). Among all PGRs treatments, the plant treated with 800 mg/L GA3 + seaweed extract (4 sprays) had developed seedless roselle fruit by exhibiting the smallest capsule diameter, capsule volume, and a low number of seeds. In a conclusion, the application of 800 mg/L GA3 + seaweed extract (4 sprays) was the effective concentration to produce seedless roselle fruit and maintain its postharvest quality.